Using baseline methods to identify non-technical losses in the context of smart grids - Faria, Pedro; Vale, Zita; Antunes, Pedro; Souza, André [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Demand response has gained increasing importance in the context of competitive electricity markets and smart grid environments. In addition to the importance that has been given to the development of business models for integrating demand response, several methods have been developed to evaluate the consumers' performance after the participation in a demand response event. The present paper uses those performance evaluation methods, namely customer baseline load calculation methods, to determine the expected consumption in each period of the consumer historic data. In the cases in which there is a certain difference between the actual consumption and the estimated consumption, the consumer is identified as a potential cause of non-technical losses. A case study demonstrates the application of the proposed method to real consumption data. © 2013 IEEE.
Keywords: Customer baseline load; demand response; nontechnical losses; performance evaluation methods; smart grid; Customer baseline loads; Demand response; Evaluation methods; Non-technical loss; Smart grid; Smart power grids